The Role of Inquiry and Problem-Solving Strategies in Arabic Language for Intermediate and Preparatory Levels (Journal of the College of Basic Education, 2026)
The weakness of our students' Arabic language skills today is evident in their reading comprehension, proficiency, and culture. This is compounded by the prevalence of linguistic and grammatical errors among many teachers themselves, and their inability to describe their feelings in classical Arabic. This, in turn, negatively impacts students' language skills, and the prevalence of linguistic errors that continually appear in various situations in students' lives, even at various stages of their education. Hence, the problem of weakness in the acquisition and teaching of Arabic language skills becomes apparent, and they are somewhat absent. Listening to correct classical Arabic is rare, and oral recitations are negligible when measured against their importance as the master of recitations. Dr. Taha Hussein expressed his opinion on the difficulty of the language. He believes that Arabic is not taught in our schools, but rather something foreign is taught in these schools, unrelated to life, nor to the students' minds and feelings. How difficult this language is! A phrase frequently repeated by Arabic speakers and non-native speakers. If they were fair, they would say: "How sterile the means and methods used to teach this language are!" Yes, the difficulty lies not in the language itself or its grammar, but rather in the methods and approaches used to teach it. These must be developed to suit the students' ages and educational level. Among the problems facing Arabic language teachers are the use of traditional methods and approaches in the curricula and the lack of participation in setting educational objectives. Among the problems facing Arabic language department students are the instructors' avoidance of using classical Arabic when presenting the material, their reliance on colloquial language, the failure to connect theory with practice, and the failure to take into account individual differences among learners. These are a group of problems that prevent language students from speaking classical Arabic.